Stress Concentration at Notches - Savruk, Mykhaylo P.; Kazberuk, Andrzej; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book compiles solutions of linear theory of elasticity problems for isotropic and anisotropic bodies with sharp and rounded notches. It contains an overview of established and recent achievements, and presents the authors' original solutions in the field considered with extensive discussion. The volume demonstrates through numerous, useful examples the effectiveness of singular integral equations for obtaining exact solutions of boundary problems of the theory of elasticity for bodies with cracks and notches. Incorporating analytical and numerical solutions of the problems of stress concentrations in solid bodies with crack-like defects, this volume is ideal for scientists and PhD students dealing with the problems of theory of elasticity and fracture mechanics. Stands as a modern and extensive compendium of solutions to the problems of linear theory of elasticity of isotropic and anisotropic bodies with sharp and rounded notches; Adopts a highly reader-friendly layout of tables, charts, approximation formulas suitable for use in research and engineering practice; Presents stress concentration factors calculated for blunt notches as well as smooth transition to the stress intensity factors for sharp notches; Includes a comprehensive survey of established and recent achievements in the field.
Method of Singular Integral Equations in Application to Problems of the Theory of Elasticity -- Stress Distribution in Elastic Plane with a Semi-infinite Notch -- Elastic Plane with Semi-infinite Notch and Cracks -- Deformation Fracture Criterion for Bodies with Notches -- Stress Concentration Near Hole in Elastic Plane -- Periodic System of Closely Spaced Holes in Elastic Plane -- Edge Notches in Elastic Half-plane -- Rectangular Specimens with Edge Notches -- Disc Specimens with Notches -- Antiplane Deformation of Elastic Bodies with Notches and Cracks -- Stress Concentration Near Notch in Anisotropic body -- Stress Concentration Near Notches in a Quasi-Orthotropic Body.
Keywords: Mechanics, Applied; Engineering mathematics; Engineering -- Data processing; Mechanics; Integral equations; Engineering Mechanics; Mathematical and Computational Engineering Applications; Classical Mechanics; Integral Equations